YouTube triggers Phubbing and FoMO behavior in generation Z - Annisa, Dona Fitri; Erwinda, Lira; Syahputra, Yuda; Septian, Muhammad Rezza (Academia Edu Cendekia Indonesia (AEDUCIA), 2023)
Youtube, as a giant video platform, has had a huge impact on the behavior and habits of generation Z. Phubbing (Phone Snubbing) and FoMO (Fear of Missing Out) are two psychological phenomena that can be related to the use of Youtube and social media in general. It is always important to understand and manage digital behavior patterns wisely to create a healthy balance between the virtual world and the real world. This research uses a quantitative approach with descriptive methods. Sampling used random sampling techniques, the sample in this study was 151 high school students in Padang City. The scales used in this research are the FoMO and Phubbing scales. This research uses three analyses, including: 1) descriptive test of FoMO and Phubbing in Padang City; 2) descriptive test of students' FoMO and Phubbing based on gender; 3) descriptive test of students' FoMO and Phubbing based on 1 month quota usage; 4) descriptive test of students' FoMO and Phubbing based on internet access; and 5) The connection between social media and internet access. Data were analyzed using descriptive analysis with the help of JASP software. The results of the research are: 1) Testing FoMO-Phubbing Conditions Based on Gender shows that there is no significant difference between the levels of FoMO and phubbing between male and female students, 2) Testing FoMO-Phubbing Conditions Based on 1 Month Quota, shows that the sample group that uses quota of more than 4 Gb has the highest phubbing score, then in the FoMO score, the sample group that uses cellular data quota in the 1 Gb to 4 Gb category with tethering has the highest FoMO score, 3) Testing FoMO-Phubbing Conditions Based on Internet Access shows that the score is good FoMO and phubbing students use their own internet quota access. This shows that, without dependence on a particular type of internet access, both FoMO and phubbing remain related to the use of mobile data quota. 5) The association between internet access and social media tendencies suggests that students who use tethering access to watch YouTube may have different experiences or behaviors. different in terms of FoMO (Fear of Missing Out; figure 5) and phubbing compared to those who use personal quotas to access other social media such as Instagram, Facebook, and Twitter. the results of this study remind us of the importance of considering differences in the use of internet access and social media platforms when designing educational interventions or programs aimed at reducing the negative impact of FoMO and phubbing on students.